Internally-consistent estimates of the smoking-attributable burden of lung cancer and cerebrovascular disease in the Philippines in 2008 - Bilano, Ver Luanni F. 1984-
Smoking has an immense adverse impact on human health worldwide. In the Philippines, smoking-related diseases have consistently been among the top ten causes of mortality, with cerebrovascular disease and cancer being the top two and three culprits respectively (DOH, 2000; NSO, 2008 and NSO, 2009). Nationwide surveys have repeatedly showed that approximately one-third (31-34%) of the adult population smoke (DOH, 1995; Sandoval et al., 1998; FNRI, 1999; FNRI, 2003; FNRI, 2008). Although tobacco control policies are in place locally, these fail to fully implement the provisions of the WHO Framework Convention on Tobacco Control (FCTC) and fail to satisfy evidence-based recommended criteria. To address such issues, up-to-date and quantitative measures of the health burden attributable to smoking are needed.
This study thus, aimed to obtain internally-consistent estimates of the smoking-attributable burden of lung cancer and cerebrovascular disease in the Philippines in 2008 with uncertainty intervals. The study was an analytic burden of disease and burden of risk factor assessment utilizing secondary data obtained via review of literature. Point estimates were obtained by applying the GBD and CRA methodologies and interval estimates were obtained by performing uncertainty analysis.
The smoking-attributable burden of lung cancer in the 2008 Philippine population was 64,913 (between 48,823 and 76,345) or 239 per 100,000 DALYs lost. For stroke on the other hand, the smoking-attributable burden in the 2008 Philippine population was 177,954 (between 59,154 and 309,510) or 7 per 100,000 DALYs lost. It is thus, recommended that the provisions of the WHO's FCTC be more strictly implemented in the Philippines.
Thesis (Master of Science in Public Health, Biostatistics)--University of the Philippines Manila, April 2012.
Available to the general public.
Keywords: Lung Neoplasms; Smoking